Global View of the Clostridium thermocellum Cellulosome Revealed by Quantitative Proteomic Analysis - Gold, Nicholas D. (American Society for Microbiology, 2007)
A metabolic isotope-labeling strategy was used in conjunction with nano-liquid chromatography-electrospray ionization mass spectrometry peptide sequencing to assess quantitative alterations in the expression patterns of subunits within cellulosomes of the cellulolytic bacterium Clostridium thermocellum, grown on either cellulose or cellobiose. In total, 41 cellulosomal proteins were detected, including 36 type I dockerin-containing proteins, which count among them all but three of the known docking components and 16 new subunits. All differential expression data were normalized to the scaffoldin CipA such that protein per cellulosome was compared for growth between the two substrates. Proteins that exhibited higher expression in cellulosomes from cellulose-grown cells than in cellobiose-grown cells were the cell surface anchor protein OlpB, exoglucanases CelS and CelK, and the glycoside hydrolase family 9 (GH9) endoglucanase CelJ. Conversely, lower expression in cellulosomes from cells grown on cellulose than on cellobiose was observed for the GH8 endoglucanase CelA; GH5 endoglucanases CelB, CelE, CelG; and hemicellulases XynA, XynC, XynZ, and XghA. GH9 cellulases were the most abundant group of enzymes per CipA when cells were grown on cellulose, while hemicellulases were the most abundant group on cellobiose. The results support the existing theory that expression of scaffoldin-related proteins is coordinately regulated by a catabolite repression type of mechanism, as well as the prior observation that xylanase expression is subject to a growth rate-independent type of regulation. However, concerning transcriptional control of cellulases, which had also been previously shown to be subject to catabolite repression, a novel distinction was observed with respect to endoglucanases.